MENC handbook of research on music learning - Colwell, Richard; Webster, Peter Richard, 1947-; Oxford University Press; MENC, the National Association for Music Education (U.S.) (New York : Oxford University Press, 2011)
The MENC Handbook of Research on Music Learning, Volumes 1 and 2 brings together the best and most current research on methods for music learning, focusing squarely on the profession's empirical and conceptual knowledge of how students gain competence in music at various ages and in different contexts. The collection of chapters, written by the foremost figures active in the field, takes a broad theoretical perspective on current, critical areas of research, including music development, music listening and reading, motivation and self-regulated learning in music, music perception, and movement. The book's companion volume, Applications, builds an extensive and solid position of practice upon the frameworks and research presented here. Throughout both volumes in this essential set, focus is placed on the musical knowledge and musical skills needed to perform, create, understand, reflect on, enjoy, value, and respond to music. A key point of emphasis rests on the relationship between music learning and finding meaning in music, and as music technology plays an increasingly important role in learning today, chapters move beyond exclusively formal classroom instruction into other forms of systematic learning and informal instruction [Publisher description]
Volume 1. Strategies. -- How learning theories shape our understanding of music learners / Susan A. O'Neill and Yaroslav Sensyshyn -- Construction of music learning / Peter R. Webster -- Roles of direct instruction, critical thinking, and transfer in the design of curriculum for music learning / Richard Colwell -- Musical development : revisiting a generic theory / Keith Swanwick -- Biological and environmental factors in music cognition and learning / Steven M. Demorest -- Motivation and achievement / Lisa Linnenbrink-Garcia, Martin L. Maehr, and Paul R. Pintrich -- Motivation to learn music : a discussion of some key elements / Bret P. Smith -- volume 2. Applications. -- Contemporary research on music listening : a holistic view / Rob E. Dunn -- The acquisition of music reading skills / Donald A. Hodges and D. Brett Nolker -- Music, movement, and learning / Carlos R. Abril -- Self-regulation of musical learning : a social cognitive perspective on developing performance skills / Gary E. McPherson and Barry J. Zimmerman -- Research on elementary and secondary school singing / Kenneth H. Phillips and Sandra M. Doneski -- Music learning in special education : focus on autism and developmental disabilities / Elise S. Sobol -- Music learning in early childhood : a review of psychological, educational, and neuromusical research / Wilfried Gruhn
Includes bibliographical references and index
Keywords: Music -- Instruction and study; Musical ability